Dynamic hydrographic and water-quality variations in the northwestern Arabian Gulf, a sinking zone of reverse estuarine circulation. (June 2022) - Yamamoto, Takahiro; Madhusoodhanan, Rakhesh; Al-Said, Turki; Ahmed, Ayaz; Fernandes, Loreta; Nithyanandan, Manickam; Thuslim, Fathima; Alghunaim, Aws; Al-Zekri, Waleed; Naqvi, S. Wajih A.; Al-Yamani, Faiza
Abstract: Continuous measurements of hydrographic, hydrodynamic, and water quality showed marked diurnal, tidal, and seasonal variabilities in Kuwait Bay, a stressed coastal system in the northwestern Arabian/Persian Gulf. Advection of water masses and seasonality in vertical mixing regulated the Bay's hydrographic and water quality properties. Intensive stratification in summer had substantial implications on the Bay environment. Kuwait Bay constantly exports dense bottom water laden with dissolved inorganic nutrients and organic matter to the central basin of the Gulf. The export was largest in August under strong water column stratification. These in-situ findings agreed well with earlier studies that corroborated Kuwait Bay as an important area where the phenomenon of reverse estuarine circulation originates in the Gulf. Thus, Kuwait Bay is a significant source of nutrients and organic matter to the Gulf Deep Water that flows into the core of the oxygen minimum zone in the northwestern Indian Ocean. Highlights: Dynamic diurnal hydrographic and water-quality variations with marked seasonality Advection of water masses and vertical mixing contributes to the variability Constant export of dense water mass from Kuwait Bay to the Arabian/Persian Gulf The largest export in August when the water column stratified